1999
DOI: 10.1097/00004872-199917010-00013
|View full text |Cite
|
Sign up to set email alerts
|

Renin–angiotensin system and fibronectin gene expression in Dahl Iwai salt-sensitive and salt-resistant rats

Abstract: These results demonstrate that the expression of tissue angiotensinogen, AT1 and fibronectin mRNAs is regulated differently in Dahl Iwai salt-sensitive and salt-resistant rats, and indicate that salt-mediated hypertension activates the cardiac fibronectin gene independently of the tissue renin-angiotensin system and stimulates the aortic fibronectin gene with activation of the tissue renin-angiotensin system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 39 publications
3
21
0
1
Order By: Relevance
“…However, Dahl-S rats fed a normal diet demonstrated lower plasma and tissue angiotensin II than Dahl-R rats, but salt loading did not cause significant changes in angiotensin II levels in either strain. 31,32 Thus, it is unlikely that angiotensin II is involved in the pathogenesis of insulin resistance in the Dahl-S rat on a high-salt diet.…”
Section: Discussionmentioning
confidence: 99%
“…However, Dahl-S rats fed a normal diet demonstrated lower plasma and tissue angiotensin II than Dahl-R rats, but salt loading did not cause significant changes in angiotensin II levels in either strain. 31,32 Thus, it is unlikely that angiotensin II is involved in the pathogenesis of insulin resistance in the Dahl-S rat on a high-salt diet.…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings in genetic hypertensive rats indicate marked interactions between a HSD, increased wall thickness, and increase in Fn. [27][28][29][30] The increase in wall thickness and Fn may contribute to the increase in vascular wall elastic modulus in proportional to the level of circumferential wall stress through an increased number of cell matrix attachments sites. 22 Interestingly, the decrease in MAP in HSD rats treated with valsartan was not associated with a significant reduction in CA wall thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that high level of mechanical stress, 15,16 stimulation of the renin angiotensin system, 17,18 as well as high sodium intake 14,19 may stimulate Fn synthesis. Because in these studies the level of wall stress was high, it is difficult to distinguish its role from that of sodium or renin angiotensin system.…”
Section: Arterial Wall Hypertrophy and Compositionmentioning
confidence: 97%